1998
DOI: 10.1093/hmg/7.5.895
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct tumor suppressor loci within chromosome 11p15 implicated in breast cancer progression and metastasis

Abstract: Chromosome 11p15 has attracted considerable attention because of the biological importance of this region to human disease. Apart from being an important tumor suppressor locus showing loss of heterozygosity (LOH) in several adult and childhood cancers, 11p15 has been shown by linkage analysis to harbor the gene(s) for the Beckwith-Wiedemann syndrome. Furthermore, the clustering of known imprinted genes in the 11p15.5 region suggests that the target gene may also be imprinted. However, positional cloning effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…1). 6 We constructed a 500 kb genomic contig (data not shown) that includes the critical region between D11S1760 and D11S1331. Using a PCR-based screening method, we initially isolated PAC and BAC clones that contained D11S1760 and D11S1331 markers.…”
Section: Localization Of Ilk To the Loh Region On Chromosome 11p155mentioning
confidence: 99%
See 2 more Smart Citations
“…1). 6 We constructed a 500 kb genomic contig (data not shown) that includes the critical region between D11S1760 and D11S1331. Using a PCR-based screening method, we initially isolated PAC and BAC clones that contained D11S1760 and D11S1331 markers.…”
Section: Localization Of Ilk To the Loh Region On Chromosome 11p155mentioning
confidence: 99%
“…1,3-5 LOH analyses have defined regions of deletion associated with metastasis on chromosomes 3p21, 15q14, 16q22 and 11p15. 2,6 Frequent genetic alterations on chromosome 11p15 suggest a crucial role for this region in breast 6,7 and other adult 8 -12 and childhood cancers. [13][14][15][16][17] More recently, we have mapped 2 distinct regions on chromosome 11p15.5 that are subject to LOH during breast tumor progression and metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sizes and quantity of marker alleles were evaluated by a semiautomated analysis using GENESCAN software, version 3.1, and the GENOTYPER software package, version 2.0 (Applied Biosystems, USA). Allelic loss was defined as a more than 70% reduction in the tumour peak area compared to the peak area of corresponding normal tissue (Karnik et al, 1998). PCR with methylation-specific primers (MSP-PCR) was used to assess the promoter methylation of the CDKN2A.…”
Section: Dna Amplification and Loh Analysismentioning
confidence: 99%
“…In addition, there were several reports of LOH in various kinds of cancers at this locus. In this region, there were two distinct tumour-suppressor loci that implicated breast cancer progression and metastasis (Karnik et al, 1998). It is suggested that an LOH of 11p15.5 might relate to poor prognosis of nonsmall-cell lung cancer (Bepler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%